Scoping out noisy galvanic vestibular stimulation: a review of the parameters used to improve postural control - McLaren, Ruth; Smith, Paul F.; Taylor, Rachael L.; Niazi, Imran Khan; Taylor, Denise (Frontiers in Neuroscience, 2023)
Objective Noisy galvanic vestibular stimulation (nGVS) has been used to facilitate vestibular function and improve gait and balance in people with poor postural control. The aim of this scoping review is to collate, summarize and report on the nGVS parameters that have been used to augment postural control. Method A systematic scoping review was conducted up to December 2022. Data were extracted and synthesized from 31 eligible studies. Key nGVS parameters were identified, and the importance of these parameters and their influence on postural control evaluated. Results A range of nGVS parameters have been used to augment postural control, including; noise waveform, amplitude, frequency band, duration of stimulation, method of amplitude optimization, size and composition of electrodes and the electrode skin interface. Conclusion Systematic evaluation of the individual parameters that can be manipulated in the nGVS waveform identified that a broad array of settings have been utilized in each parameter across the studies. Choices made around the electrode and electrode-skin interface, as well as the amplitude, frequency band, duration and timing of the waveform are likely to influence the efficacy of nGVS. The ability to draw robust conclusions about the selection of optimal nGVS parameters to improve postural control, is hindered by a lack of studies that directly compare parameter settings or consider the variability in individuals’ response to nGVS. We propose a guideline for the accurate reporting of nGVS parameters, as a first step toward establishing standardized stimulation protocols.